Long-Term Persisting SARS-CoV-2 RNA and Pathological Findings: Lessons Learnt From a Series of 35 COVID-19 Autopsies - Maccio, Umberto; Zinkernagel, Annelies S.; Schuepbach, Reto; Probst-Mueller, Elsbeth; Frontzek, Karl; Brugger, Silvio D.; Hofmaenner, Daniel Andrea; Moch, Holger; Varga, Zsuzsanna (Frontiers in Medicine, 2022)
Background: Long-term perspective of COVID-19 including the interaction between persisting viral-RNA and specific tissue involvement is a challenging issue. In this study, we addressed the chronological correlation (after first clinical diagnosis and postmortem) between SARS-CoV-2 RNA and organ involvement. Methods: The presence of postmortem SARS-CoV-2 RNA from 35 complete COVID-19 autopsies were correlated with time interval between first diagnosis of COVID-19 and death and with its relationship to morphologic findings. Results: SARS-CoV-2 RNA can be evident up to 40 days after first diagnosis and can persist to 94 hours after death. Postmortal SARS-CoV-2 RNA were mostly positive in lungs (70%) and trachea (69%) but all investigated organs were positive with different frequency. Late stage tissue damage was evident up to 65 days after initial diagnosis in several organs. Positivity for SARS-CoV-2 RNA in pulmonary swabs correlated with diffuse alveolar damage (p=0.0009). No correlation between positive swabs and other morphologic findings was present. Cerebral (p=0.0003) and systemic hemorrhages (p=0.009), cardiac thrombi (p=0.04) and ischemic events (p=0.03) were more frequent in the first wave, whereas bacterial pneumonia (p=0.03) was more prevalent in the second wave. No differences in biometric data, clinical comorbidities and other autopsy findings were found. Conclusions: Our data provide evidence not only of long-term postmortal persisting SARS-CoV-2 RNA but also of tissue damage several weeks after first diagnosis of SARS-CoV-2 infection. Additional conditions such as concomitant bacterial pulmonary superinfection, lung aspergillosis, thromboembolic phenomena and hemorrhages can further worsen tissue damage. Funding: No external funding was necessary for this study.